IEEE PES General Meeting 2010
DOI: 10.1109/pes.2010.5589316
|View full text |Cite
|
Sign up to set email alerts
|

How to estimate the value of service reliability improvements

Abstract: Abstract--A robust methodology for estimating the value of service reliability improvements is presented. Although econometric models for estimating value of service (interruption costs) have been established and widely accepted, analysts often resort to applying relatively crude interruption cost estimation techniques in assessing the economic impacts of transmission and distribution investments. This paper first shows how the use of these techniques can substantially impact the estimated value of service imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…Lupski, PSEG, 2017, personal communication). We then applied data from Sullivan et al (2013) to monetize the cost of power outages to customers. Sullivan et al (2013) provided estimated average electric customer interruption costs by customer type-including residential, small commercial, and medium and large commercial-and duration of power outages.…”
Section: E631mentioning
confidence: 99%
See 1 more Smart Citation
“…Lupski, PSEG, 2017, personal communication). We then applied data from Sullivan et al (2013) to monetize the cost of power outages to customers. Sullivan et al (2013) provided estimated average electric customer interruption costs by customer type-including residential, small commercial, and medium and large commercial-and duration of power outages.…”
Section: E631mentioning
confidence: 99%
“…We then applied data from Sullivan et al (2013) to monetize the cost of power outages to customers. Sullivan et al (2013) provided estimated average electric customer interruption costs by customer type-including residential, small commercial, and medium and large commercial-and duration of power outages. We used the U.S. Energy Information Administration number of retail customers by state for the State of New York to obtain a distribution of customer types, and we assumed that the power outages affect customer types in a manner consistent with the distribution of customer types across the state.…”
Section: E631mentioning
confidence: 99%
“…We use the duration of the event to determine the impact of service based on customer class. Since value of service does not increase linearly, we assign the value of service impact based on the closest match to durations of 0, 1, 4, and 8 hours and their expected cost to different customer classes [15]. We also cap the longest duration at 8 hours, since some studies have shown that the impact of the outage flattens out and does not necessarily lead to additional economic losses to the customer.…”
Section: Value Of Servicementioning
confidence: 99%
“…In [16], Costa et al presents the benefit based on typical reliability indexes without concerning the value of reliability itself. For a guide to outage valuation see [34]; moreover [35] analyzes problems of usual practices for reliability improvement valuation. Further information can be founded in [14].…”
Section: Reliability Supportmentioning
confidence: 99%